Application of double-aromatic ring compound as positive active material of solid-state lithium battery
By using specific biaromatic cyclic compounds as the positive electrode active substance in solid-state lithium batteries and combining with solid electrolytes, the problem of insufficient discharge voltage of existing solid-state lithium batteries is solved, and high discharge voltage and excellent electrochemical performance are achieved.
Patent Information
- Application Number
- CN202510101993.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
AI Technical Summary
The discharge voltage of existing organic positive electrode solid-state lithium batteries is less than 3.5V, which affects the battery capacity and circulation rate.
A specific biaromatic cyclic compound is used as the positive electrode active substance of solid lithium batteries, and combined with solid electrolytes, a metal lithium battery with high discharge voltage is prepared.
The average discharge voltage of metal lithium batteries has been achieved above 3.9V, which is significantly better than the existing technology, and has better electrochemical performance, larger capacity and slower attenuation.
Smart Images

Figure CN119890301A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery preparation, and specifically relates to the application of a diaromatic ring compound as a positive electrode active material for a solid-state lithium battery. Background Art
[0002] With the continuous growth of global energy demand and increasing concern for environmental sustainability, the development of high-performance battery technology is particularly important. Lithium-ion batteries have become the mainstream choice for portable electronic devices and electric vehicles due to their high energy density, long cycle life and relatively high safety.
[0003] As one of the types of lithium batteries, solid-state lithium batteries (SSLB) have become an important development direction of the next generation of battery technology due to their high energy density, long cycle life and high safety. Among them, organic positive electrode solid-state lithium batteries have gradually become one of the research directions of solid-state lithium batteries due to their unique advantages over other solid-state metal lithium batteries, such as high specific capacity and good electrochemical stability.
[0004] However, the discharge voltage of the organic cathode solid-state battery in the prior art is less than 3.5V, which affects the electrochemical properties of the solid-state lithium battery, such as the capacity and cycle rate. For example, Deng et al. used 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinoline dimethane (F4TCNQ) with a voltage of 3.4V as the cathode and solid PEO-LLZTO as the electrolyte. At a current density of 10mAg -1 , specific capacity is 80mAhg -1 For example, Sun et al. used an organic cathode material, phenanthrene triquinone (PQ), and a halide solid electrolyte, Li2ZrCl6, to develop an all-solid-state lithium battery with an average discharge voltage of 2.74 V and a specific capacity of 248 mAh g -1 . Summary of the invention
[0005] The present invention finds that by using specific diaromatic ring compounds as positive electrode active materials for solid-state lithium batteries, the discharge voltage of a solid-state metal lithium battery prepared based on the positive electrode active materials can reach above 3.9V, which is significantly better than the discharge voltage of existing organic positive electrode solid-state batteries.
[0006] In order to achieve the above object, the present invention can adopt the following technical solutions:
[0007] In one aspect, the present invention provides a solid-state lithium battery, the solid-state lithium battery comprising a positive electrode active material, the positive electrode active material comprising one or more of the diaromatic ring compounds shown in Formula I:
[0008]
[0009] In the formula, R1 and R2 are independently selected from S, O or substituted or unsubstituted amino groups, and the substituent of the substituted amino group is an alkyl group.
[0010] Preferably, in the above-mentioned N-substituted alkylamine group, the alkyl group is a branched hydrocarbon group or a straight hydrocarbon group.
[0011] More preferably, the above alkyl group is a straight-chain hydrocarbon group, and the number of carbon atoms in the straight-chain hydrocarbon group is ≤5.
[0012] More preferably, the above-mentioned biaromatic ring compound is selected from one or more combinations of phenoxathiol, 5,10-dihydro-5,10-dimethylphenazine, 10-methylphenothiazine or thianthrene.
[0013] Preferably, the above-mentioned solid-state lithium battery also includes a solid electrolyte, the solid electrolyte includes a substrate and an electrolyte material on the surface of the substrate, the electrolyte material includes a polymer and a lithium salt; or the electrolyte material includes a polymer, a lithium salt and an ionic liquid.
[0014] More preferably, the solid electrolyte satisfies one or more of the following conditions: (a) the polymer is selected from one or more of PDADMATFSI, PDADMAFSI or PDADMAPF6; (b) the lithium salt is selected from one or more combinations of LiTFSI, LiFSI or LiPF6; (c) the ionic liquid is PYR 13 TFSI and / or PYR 13 FSI; (d) the electrolyte material includes a polymer and a lithium salt, and the mass ratio of the polymer and the lithium salt is (1-3):(1-2); (e) the electrolyte material includes a polymer, a lithium salt and an ionic liquid, and the mass ratio of the polymer, the lithium salt and the ionic liquid is (1-3):(1-2):(2-3); (f) the thickness of the substrate is (e) the thickness of the substrate is 0.03mm-10mm; (g) the substrate is a membrane material prepared from natural wood fiber slurry.
[0015] More preferably, the method for preparing the solid electrolyte comprises: mixing a polymer, a lithium salt, an ionic liquid and a first solvent to obtain a first mixture; then coating the first mixture on a substrate, and first drying to obtain a solid electrolyte.
[0016] More preferably, the preparation method of the above-mentioned solid electrolyte satisfies one or more of the following conditions: (i) the first solvent is selected from one or more combinations of N-methylpyrrolidone, N,N-dimethylformamide or acetone; (ii) the first drying condition includes: the drying temperature is 30°C-100°C, and the drying time is 1h-36h.
[0017] Preferably, the positive electrode active material further includes a conductive material and a binder.
[0018] More preferably, the above-mentioned positive electrode active material satisfies one or more of the following conditions: (A) the conductive material is selected from one or more combinations of SuperP, carbon nanotubes, graphene or conductive carbon black; (B) the binder is selected from one or more combinations of PDADMATFSI, PVDF or sodium alginate; (C) the mass ratio of the diaromatic ring compound, the conductive material and the binder is (4-8): (1-5): 1.
[0019] More preferably, the solid-state lithium battery includes a positive electrode, the positive electrode includes a positive electrode plate and a positive electrode active material on the surface of the positive electrode plate, and the preparation method of the positive electrode includes: mixing the positive electrode active material and a second solvent, grinding to obtain a second mixture; mixing the second mixture with the second solvent to obtain a third mixture; coating the third mixture on the positive electrode plate, and drying to obtain the positive electrode.
[0020] More preferably, the preparation method of the positive electrode satisfies one or more of the following conditions: (I) the thickness of the positive electrode active material is 0.025 mm-10 mm; (II) the positive electrode plate is an aluminum current collector, and the aluminum content in the aluminum current collector is greater than 5%; (III) the second solvent is selected from one or more combinations of N-methylpyrrolidone, N,N-dimethylformamide or acetone; (IV) in the second mixture, the total mass concentration of the diaromatic ring compound, the conductive material and the adhesive is 0.001 g / ml-1 g / ml; (V) the second drying temperature is 30°C-120°C.
[0021] In another aspect, the present invention provides an application of a diaromatic ring compound as a positive electrode active material for a solid-state lithium battery. The structural formula of the diaromatic ring compound is shown below:
[0022] In the formula, R1 and R2 are independently selected from S, O or substituted or unsubstituted amino groups, and the substituent of the substituted amino group is an alkyl group.
[0023] More preferably, the above-mentioned biaromatic ring compound is selected from phenoxathiol, 5,10-dihydro-5,10-dimethylphenazine, 10-methylphenothiazine or thianthrene.
[0024] The beneficial effects of the present invention include:
[0025] (1) In the present invention, the metal lithium battery prepared by using the diaromatic ring compound shown in Formula I as the positive electrode active material in the solid-state lithium battery has a higher voltage than the existing solid-state lithium battery. The average discharge voltage of the metal lithium battery in the present invention can be as high as 3.9V or more, which is much higher than the existing organic positive electrode-based solid-state battery (less than 3.5V).
[0026] (3) The present invention uses the diaromatic ring compound shown in Formula I as a positive electrode active material in a solid-state lithium battery and an ionic liquid electrolyte metal lithium battery for comparison. The electrochemical performance of the compound used in the solid-state lithium battery is better, such as a higher average voltage, a larger battery capacity, and a slower decay. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 CV test results of the metal battery prepared in Example 5;
[0028] Figure 2 CV test results of the metal battery prepared in Example 6;
[0029] Figure 3 CV test results of the metal battery prepared in Example 7;
[0030] Figure 4 CV test results of the metal battery prepared in Example 8;
[0031] Figure 5 CV test results of the metal battery prepared in Comparative Example 1;
[0032] Figure 6 CV test results of the metal battery prepared in Comparative Example 2;
[0033] Figure 7 CV test results of the metal battery prepared in Comparative Example 3;
[0034] Figure 8 CV test results of the metal battery prepared in Comparative Example 4;
[0035] Fig. 9 100 charge-discharge cycle test results of the metal batteries prepared in Example 5 and Comparative Example 1;
[0036] Fig.10 100 charge-discharge cycle test results of the metal batteries prepared in Example 6 and Comparative Example 2;
[0037] Fig.11 100 charge-discharge cycle test results of the metal batteries prepared in Example 7 and Comparative Example 3;
[0038] Fig.12 100 charge-discharge cycle test results of the metal batteries prepared in Example 8 and Comparative Example 4;
[0039] Fig.13 The rate test results of the metal battery prepared in Example 5;
[0040] Fig.14 The rate test results of the metal battery prepared in Example 6;
[0041] Fig.15 The rate test results of the metal battery prepared in Example 7;
[0042] Fig.16 This is the rate test result of the metal battery prepared in Example 8. DETAILED DESCRIPTION
[0043] The examples are provided to better illustrate the present invention, but the present invention is not limited to the examples. Therefore, those skilled in the art may make non-essential improvements and adjustments to the implementation scheme according to the above invention content, which still fall within the protection scope of the present invention.
[0044] The terms used herein are only used to describe specific embodiments and are not intended to limit the present disclosure. Unless the context has a significantly different meaning, expressions in the singular include expressions in the plural. As used herein, it should be understood that terms such as "include", "have", "include" are intended to indicate the presence of features, numbers, operations, components, parts, elements, materials or combinations. The terms of the present invention are disclosed in the specification, and are not intended to exclude the possibility that one or more other features, numbers, operations, components, parts, elements, materials or combinations thereof may exist or may be added. As used herein, " / " may be interpreted as "and" or "or", depending on the circumstances.
[0045] An embodiment of the present invention provides a solid-state lithium battery, the solid-state lithium battery comprising a positive electrode and a solid electrolyte, the positive electrode comprising a diaromatic ring compound, the diaromatic ring compound comprising one or more compounds shown in Formula I:
[0046]
[0047] In the formula, R1 and R2 are independently selected from S, O or substituted or unsubstituted amino groups, and the substituent of the substituted amino group is an alkyl group.
[0048] It should be noted that in the present invention, specific diaromatic ring compounds (such as phenoxathiol (PHX), 5,10-dihydro-5,10-dimethylphenazine (PNZ), 10-methylphenothiazine (PTZ) or thianthrene (TT)) can be used as positive electrodes and combined with solid electrolytes to assemble organic cathode solid-state batteries. The discharge voltage of the prepared polymer solid-state battery (which can reach 3.9V) is higher than that of existing organic cathode solid-state batteries (lower than 3.5V), and even higher than the 3.6V of commercially used lithium iron phosphate batteries and the 3.7V of ternary (nickel cobalt manganese oxide) positive electrodes; in addition, the organic cathode solid-state battery in the present invention can still maintain 100mAh g at a high current of 1C. -1The existing organic cathode solid-state batteries have poor electrical conductivity, which means they can only achieve a higher battery capacity below 1C.
[0049] It should also be noted that the electrochemical performance of the organic cathode solid-state battery assembled by the present invention using a specific diaromatic ring compound as the positive electrode combined with a solid electrolyte is better than that of a liquid battery combined with an ionic liquid electrolyte as the positive electrode. For example, the assembled solid-state battery has better capacitance, a higher average voltage, and slower decay.
[0050] In some specific examples, in the above-mentioned N-substituted alkylamine group, the alkyl group is a branched hydrocarbon group or a straight-chain hydrocarbon group; for example, the branched hydrocarbon group can be methyl, ethyl, isopropyl, tert-butyl or isobutyl, etc.; the straight-chain hydrocarbon group can also be methyl, ethyl, n-propyl or n-butyl, etc.
[0051] In some specific examples, the alkyl group is a straight-chain hydrocarbon group, and the number of carbon atoms in the straight-chain hydrocarbon group is ≤5; for example, methyl, ethyl, n-propyl, n-butyl or n-pentyl.
[0052] In some specific examples, the above-mentioned bicyclic aromatic ring compound is selected from one or more combinations of phenoxathiol, 5,10-dihydro-5,10-dimethylphenazine, 10-methylphenothiazine or thianthracene.
[0053] It should be noted that the biaromatic ring compound in the present invention may preferably be phenoxathiol (PHX, ), 5,10-dihydro-5,10-dimethylphenazine (PNZ, ), 10-methylphenothiazine (PTZ, ) or thianthrene (TT, ); of course, it can be a combination of the above substances; the electrochemical performance of the metal lithium battery prepared with the above-mentioned diaromatic ring compounds as the positive electrode is better than that of the metal lithium battery prepared with other diaromatic ring compounds, among which phenoxathiol (PHX) is more preferred (the battery assembled with phenoxathiol (PHX) positive electrode and the solid electrolyte can excite the two active sites of the S and O groups of PHX, so that two redox peaks appear in the CV test, realizing the high capacity and high voltage of the lithium battery).
[0054] In some specific examples, the solid electrolyte includes a substrate and an electrolyte material on the surface of the substrate, the electrolyte material includes a polymer and a lithium salt; or the electrolyte material includes a polymer, a lithium salt and an ionic liquid.
[0055] Specifically, the electrolyte material may include a polymer and a lithium salt; in addition, the electrolyte material may further include an ionic liquid, which may increase the ionic conductivity of the solid electrolyte.
[0056] In some specific examples, the solid electrolyte satisfies one or more of the following conditions:
[0057] (a) the polymer is selected from one or more of PDADMATFSI (poly(diallyldimethylammonium)bis(trifluoromethanesulfonyl)imide), PDADMAFSI (poly(diallyldimethylammonium)bis(fluorosulfonyl)imide) or PDADMAPF6 (poly(diallyldimethylammonium)hexafluorophosphate); specifically, the polymer used in the preparation of the solid electrolyte in the present invention is well known in the art, and the above-mentioned polymer or combination is preferred, which is more suitable for the solid-state lithium battery in the present invention;
[0058] (b) the lithium salt is selected from one or more combinations of LiTFSI, LiFSI or LiPF6; specifically, the lithium salt in the present invention is well known in the art, and the above-mentioned lithium salt or combination is preferred, which is more suitable for the solid-state lithium battery in the present invention;
[0059] (c) The ionic liquid is PYR 13 TFSI and / or PYR 13 FSI; Specifically, the lithium salt in the present invention is well known in the art, and the above-mentioned ionic liquid or combination is preferred, which is more suitable for the solid-state lithium battery in the present invention;
[0060] (d) the electrolyte material includes a polymer and a lithium salt, and the mass ratio of the polymer to the lithium salt is (1-3):(1-2), such as 2:1, 2.5:1 or 1:1.5;
[0061] (e) The electrolyte material includes a polymer, a lithium salt and an ionic liquid, and the mass ratio of the polymer, the lithium salt and the ionic liquid is (1-3):(1-2):(2-3), such as 2:1:2, 2.5:1:2.5 or 1:1.5:2, etc.;
[0062] (f) The thickness of the substrate is 0.03 mm to 10 mm, such as 0.05 mm, 1 mm, 3 mm, 5 mm, 7 mm or 9 mm;
[0063] (g) The substrate is a membrane-like material prepared from natural wood fiber slurry; specifically, the solid electrolyte in the solid-state lithium battery of the present invention is prepared using the membrane-like material prepared from natural wood fiber slurry as the substrate, and the preparation cost is better than that of existing polyimide films, polyethylene non-woven fabrics, polypropylene non-woven fabrics, glass fiber non-woven fabrics, cellulose non-woven fabrics or polytetrafluoroethylene non-woven fabrics, etc.; and the electrochemical performance is excellent.
[0064] In some specific examples, the method for preparing the solid electrolyte includes: mixing a polymer, a lithium salt, an ionic liquid and a first solvent to obtain a first mixture; then coating the first mixture on a substrate, and first drying to obtain a solid electrolyte.
[0065] In some specific examples, the preparation method of the solid electrolyte satisfies one or more of the following conditions:
[0066] (i) the first solvent is selected from one or more combinations of N-methylpyrrolidone, N,N-dimethylformamide or acetone;
[0067] (ii) The first drying conditions include: a drying temperature of 30°C-100°C, such as 40°C, 50°C, 60°C, 70°C, 80°C or 90°C; a drying time of 1h-36h, such as 5h, 10h, 15h, 20h, 25h or 30h.
[0068] In some specific examples, the positive electrode active material further includes a conductive material and a binder.
[0069] In some specific examples, the positive electrode active material satisfies one or more of the following conditions:
[0070] (A) The conductive material is selected from one or more combinations of SuperP, carbon nanotubes, graphene or conductive carbon black; specifically, the conductive material is well known in the art, such as the above-mentioned materials;
[0071] (B) the binder is selected from one or more combinations of PDADMATFSI, PVDF or sodium alginate;
[0072] (C) The mass ratio of the diaromatic ring compound, the conductive material and the adhesive is (4-8):(1-5):1, such as 4:5:1, 5:4:1, 6:3:1, 7:2:1 or 8:1:1.
[0073] In some specific examples, a solid-state lithium battery includes a positive electrode, the positive electrode includes a positive electrode plate and a positive electrode active material on the surface of the positive electrode plate, and the preparation method of the positive electrode includes: mixing the positive electrode active material and a second solvent, grinding to obtain a second mixture; mixing the second mixture with the second solvent to obtain a third mixture; coating the third mixture on the positive electrode plate, and drying to obtain the positive electrode.
[0074] In some specific examples, the preparation method of the positive electrode satisfies one or more of the following conditions:
[0075] (I) The thickness of the positive electrode active material is 0.025 mm-10 mm; for example, 0.05 mm-9 mm, 1 mm-7 mm, 3 mm-5 mm, for example, 1 mm, 5 mm, 7 mm or 9 mm;
[0076] (II) The positive electrode plate is an aluminum current collector, and the aluminum content of the aluminum current collector is greater than 5%; specifically, the aluminum current collector is a metal material with an aluminum content greater than 5%;
[0077] (III) the second solvent is selected from one or more combinations of solvents selected from N-methylpyrrolidone, N,N-dimethylformamide or acetone;
[0078] (IV) In the second mixture, the total mass concentration of the diaromatic ring compound, the conductive material and the adhesive is 0.001 g / ml-1 g / ml; for example, 0.005 g / ml, 0.01 g / ml, 0.05 g / ml or 0.08 g / ml;
[0079] (V) The temperature of the second drying is 30°C-120°C, such as 40°C, 50°C, 70°C, 80°C, 100°C or 110°C.
[0080] The embodiment of the present invention further provides an application of a diaromatic ring compound as a positive electrode active material of a solid-state lithium battery. The structural formula of the diaromatic ring compound is as follows:
[0081] In the formula, R1 and R2 are independently selected from S, O or substituted or unsubstituted amino groups, and the substituent of the substituted amino group is an alkyl group.
[0082] In some specific examples, the bicyclic aromatic ring compound is selected from phenoxathiazine, 5,10-dihydro-5,10-dimethylphenazine, 10-methylphenothiazine or thianthracene.
[0083] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific examples, but the content of the present invention is not limited to the following examples.
[0084] 1. Preparation of positive electrode materials
[0085] Example 1
[0086] (1) 50 mg of 10-methylphenothiazine (PTZ) (a diaromatic ring compound), 40 mg of conductive carbon black, and 10 mg of a binder (polyvinylidene fluoride) were ground and mixed uniformly, and then 120 μL of N-methylpyrrolidone was added dropwise at a dosage of 20 μL each time, and then the mixture was ground and mixed uniformly to obtain a positive electrode slurry;
[0087] (2) An aluminum film is placed on a smooth glass plate, and then the positive electrode slurry is placed on one side of the aluminum film. The scraper is adjusted to a thickness of 150 μm, and then the positive electrode slurry is scraped evenly; then, after vacuum drying at 50°C for 1 hour, the temperature is raised to 70°C and drying is continued for 7 hours to obtain a positive electrode.
[0088] Example 2
[0089] The difference between Example 2 and Example 1 is that the diaromatic ring compound in Example 2 is 5,10-dihydro-5,10-dimethylphenazine (PNZ), and the other steps are the same as in Example 1 to prepare a positive electrode.
[0090] Example 3
[0091] The difference between Example 2 and Example 1 is that the diaromatic ring compound in Example 2 is phenoxathiol (PHX), and the other steps are the same as in Example 1 to prepare a positive electrode.
[0092] Example 4
[0093] The difference between Example 2 and Example 1 is that the diaromatic ring compound in Example 2 is thianthrene (TT), and the other steps are the same as in Example 1 to prepare a positive electrode.
[0094] 2. Preparation of Metal Lithium Batteries
[0095] In the following example, the preparation method of PDADMATFSI polymer is as follows: 43g LiTFSI (lithium bistrifluoromethanesulfonyl imide) is dissolved in 50ml deionized water to obtain mixed solution 1; 20g PDADMACL (20% by mass, polydiallyldimethylammonium chloride solution) is dissolved in 500ml deionized water to obtain mixed solution 2; mixed solution 1 and mixed solution 2 are mixed and stirred for 3 hours, the precipitate is filtered, and vacuum dried (100°C) for 12h to obtain pDADMATFSI polymer.
[0096] Example 5
[0097] (I) Preparation of composite polymer electrolyte
[0098] (1) dissolving 2 g of PDADMATFSI polymer in 20 mL of DMF to obtain a 35 wt % first mixed solution;
[0099] (2) dissolving 0.85 g of LiTFSI in the first mixed solution to obtain a 15 wt % second mixed solution;
[0100] (3) 2.857 g of ionic liquid (PYR 13 TFSI) is dissolved in the second mixed solution to obtain a 50wt% third mixed solution;
[0101] (4) The third mixed solution is poured on the wood fiber membrane substrate, scraped to a certain thickness, and then placed in a vacuum drying oven for drying to obtain a composite polymer solid electrolyte.
[0102] (II) Preparation of metal lithium batteries
[0103] The positive electrode prepared in Example 1 was cut into positive electrode discs with a diameter of 12 mm as the positive electrode sheet, and a lithium sheet was used as the negative electrode; the composite polymer electrolyte prepared as above was sandwiched between the positive electrode sheet and the negative electrode sheet and assembled into a CR2032 battery shell to form a button battery; specifically as follows: a polymer solid electrolyte with an area larger than that of the positive electrode and the negative electrode was placed between the positive electrode and the negative electrode, and the positive and negative electrodes were not in direct contact, the coated side of the positive electrode was in contact with the solid electrolyte, the positive and negative electrodes were aligned, and a gasket and a gasket were placed on the back of the positive electrode or the negative electrode, the number of which was 2, and then it was placed in the battery shell and sealed with a sealing machine.
[0104] Example 6
[0105] The difference between Example 6 and Example 5 is that Example 6 uses the positive electrode prepared in Example 2 to prepare a positive electrode sheet, and the other steps are the same as Example 5 to prepare a button battery.
[0106] Example 7
[0107] The difference between Example 7 and Example 5 is that Example 6 uses the positive electrode prepared in Example 3 to prepare a positive electrode sheet, and the other steps are the same as Example 5 to prepare a button battery.
[0108] Example 8
[0109] The difference between Example 8 and Example 5 is that Example 6 uses the positive electrode prepared in Example 3 to prepare a positive electrode sheet, and the other steps are the same as Example 5 to prepare a button battery.
[0110] Comparative Example 1
[0111] The positive electrode prepared in Example 1 was cut into a positive electrode disc with a diameter of 12 mm as the positive electrode sheet, and a lithium sheet with a diameter of 12 mm was used as the negative electrode. The diameter of the polypropylene separator was 16 mm. PYR containing 0.3 M LiTFSI was 13 TFSI ionic liquid electrolyte (0.3M refers to LiTFSI in PYR 13 Molar concentration of TFSI in ionic liquid, PYR 13 TFSI ionic liquid (40 μL) was dripped on the negative electrode with 20 μL, and then a polypropylene diaphragm was placed, and then 20 μL of ionic liquid was dripped on the upper layer of the diaphragm, and then the positive electrode was placed with the coated side facing the diaphragm, and finally assembled into a CR2032 battery shell to form a button battery.
[0112] Comparative Example 2
[0113] The difference between Comparative Example 2 and Comparative Example 1 is that Comparative Example 2 uses the positive electrode prepared in Example 2 to prepare a positive electrode sheet, and the other steps are the same as Comparative Example 1 to prepare a button battery.
[0114] Comparative Example 3
[0115] The difference between Comparative Example 3 and Comparative Example 1 is that Comparative Example 3 uses the positive electrode prepared in Example 3 to prepare a positive electrode sheet, and the other steps are the same as Comparative Example 1 to prepare a button battery.
[0116] Comparative Example 4
[0117] The difference between Comparative Example 4 and Comparative Example 1 is that Comparative Example 4 uses the positive electrode prepared in Example 4 to prepare a positive electrode sheet, and the other steps are the same as those in Comparative Example 1 to prepare a button battery.
[0118] 3. Metal lithium battery test
[0119] (I) Cyclic Voltammetry (CV) Test
[0120] The button cells prepared in Examples 5 to 8 and Comparative Examples 1 to 4 were subjected to cyclic voltammetry tests, specifically including: using a Donghua electrochemical workstation, testing the button cells with two electrodes, selecting a new experiment - cyclic voltammetry, setting parameters: setting the starting point according to the open circuit voltage of the battery, then setting the vertex point, i.e., the voltage window range of the CV test, and finally setting the scan rate to 50 mV / s, and performing 4 cycles of scanning. The results are as follows: Figures 1 to 8 As shown; the list is shown in Table 1 (two numbers represent two peaks).
[0121] Table 1 CV test results of metal batteries prepared in Examples / Comparative Examples
[0122]
[0123]
[0124] Combination Figures 1 to 8 And from Table 1 we can see:
[0125] Figure 1 It is a diaromatic ring compound 10-methylphenothiazine (PTZ, ) as the positive electrode and the composite solid electrolyte as the electrolyte in the lithium metal battery CV test, two groups of redox peaks appeared at 3.4V-3.5V and 3.6V-3.8V, corresponding to the redox reactions at the active sites of the N group and the S group, respectively;
[0126] Figure 2 It is a diaromatic ring compound 5,10-dihydro-5,10-dimethylphenazine (PNZ, ) as the positive electrode and the composite solid electrolyte as the electrolyte in the lithium metal battery CV test, two groups of redox peaks appeared at 2.5V-3V and 3.2V-3.8V, corresponding to the redox reactions at the two N group active sites;
[0127] Figure 3 It is a diaromatic ring compound phenoxathiol (PHX, ) as the positive electrode and the composite solid electrolyte as the electrolyte, the lithium metal battery CV test showed two groups of redox peaks at 3.8V-3.9V and 4V-4.2V, corresponding to the redox reactions at the active sites of the S group and the O group respectively; compared with the liquid electrolyte conditions, the solid electrolyte conditions are more compatible with PHX and can additionally excite the O group as an active site, which not only increases the average discharge voltage of PHX, but also achieves a higher battery capacity;
[0128] Figure 4 It is a diaromatic ring compound thianthrene (TT, ) as the positive electrode and the composite solid electrolyte as the electrolyte, a group of redox peaks appeared at 3.7V-3.9V, corresponding to the redox reaction at the active site of the S group; this means that TT is generally compatible with the solid electrolyte and cannot stimulate the two active sites; in contrast, the specific PHX as the positive electrode active material and the specific composite polymer solid electrolyte can successfully stimulate the second active site, thereby achieving higher battery performance;
[0129] Figure 5 In the CV test of a lithium metal battery with a diaromatic ring compound 10-methylphenothiazine (PTZ) as the positive electrode and an ionic liquid containing 0.3MLiTFSI as the electrolyte, two groups of redox peaks appeared at 3.3V-3.5V and 3.9V-4.0V, corresponding to the redox reactions at the active sites of the N group and the S group, respectively.
[0130] Figure 6 In the CV test of a lithium metal battery with a diaromatic ring compound 5,10-dihydro-5,10-dimethylphenazine (PNZ) as the positive electrode and an ionic liquid containing 0.3MLiTFSI as the electrolyte, two groups of redox peaks appeared at 2.8V-3V and 3.4V-3.7V, corresponding to the redox reactions at the two N group active sites.
[0131] Figure 7 In the CV test of a lithium metal battery with a diaromatic ring compound phenoxathiol (PHX) as the positive electrode and an ionic liquid containing 0.3M LiTFSI as the electrolyte, a group of redox peaks appeared at 3.9V-4.0V, corresponding to the redox reaction at the active site of the S group, and the redox peak of the O group did not appear, indicating that no redox reaction occurred;
[0132] Figure 8In the CV test of a lithium metal battery with a diaromatic ring compound thianthrene (TT) as the positive electrode and an ionic liquid containing 0.3MLiTFSI as the electrolyte, a group of redox peaks appeared at 3.8V-4.0V, corresponding to a redox reaction at one of the active sites in the two S groups, and the second active site was not successfully excited.
[0133] In summary, the embodiments have more obvious redox peaks than the comparative examples, especially the PHX substance has only one set of redox peaks in the comparative example, but two sets of redox peaks appear in the embodiments, which means that compared with the liquid electrolyte, the solid electrolyte of the present invention is more conducive to stimulating the redox active center of PHX.
[0134] (II) Cyclic charge and discharge test
[0135] The button cells prepared in Examples 5 to 8 and Comparative Examples 1 to 4 were subjected to a cyclic charge and discharge test, specifically including: using a Xinwei battery charge and discharge tester, placing the button cells on a test clip, selecting a test channel, and setting parameters: Step 1: standing for 8 hours; Step 2: charging 1.3V-4.3V, 0.1C; Step 3: discharging 1.3V-4.3V, 0.1C; Step 4: cycling, starting from Step 2, until the cycle ends after 100 cycles; in addition, the mass of the active material is generally set to 0.5mg. The test results are as follows Figures 9 to 12 As shown, the list is shown in Table 2.
[0136] Table 2 Cyclic charge and discharge test results of metal batteries prepared in Examples / Comparative Examples
[0137]
[0138] Depend on Figures 9 to 12 Combined with Table 2 above, we can know that:
[0139] First, after 100 cycles, the specific capacity increases because the ion transmission channels of the solid electrolyte are not fully opened in the initial stage. After multiple cycles, the ion transmission channels increase, which leads to an increase in the cycle specific capacity. In addition, as the charging and discharging proceeds, the battery specific capacity of the liquid electrolyte (Comparative Examples 1 to 4) decays, which means that part of the ions in the battery cannot be embedded in or removed from the electrodes, leaving only a part of the reversible ions moving between the positive and negative electrodes. Although the charge specific capacity and discharge specific capacity decrease, the battery charging and discharging gradually stabilize, and the number of ion embedding and removal gradually tends to be consistent, which leads to an increase in coulombic efficiency.
[0140] Secondly, for liquid electrolytes, there is no phenomenon of ion channel opening, so the capacity of all ionic liquid electrolyte batteries (Comparative Examples 1 to Comparative Examples 4) is attenuated; however, for solid electrolytes, the intermolecular interaction forces between different positive active materials and the same solid electrolyte are different, that is, the polarity of the unused positive electrode activity is different from that of the solid electrolyte; Obviously, the cathode material in Examples 5 and 7 has a strong polarity with the solid electrolyte, which will cause a part of the active material at the contact interface between the cathode and the solid electrolyte to dissolve into the solid electrolyte, thereby causing the battery capacity to decay. This process is caused by a variety of factors, such as the temperature increase during the battery charging and discharging process, which accelerates the dissolution of the cathode active material into the electrolyte; the high charging and discharging voltage causes the solid electrolyte to undergo side reactions, and the production of a part of the liquid byproduct will cause the cathode active material to dissolve therein. While Examples 6 and 8 have weaker polarity, which also causes them not to dissolve into the solid electrolyte interface and not to decay.
[0141] Furthermore, the specific descriptions of Comparative Examples 1 to 4 and Examples 1 to 4 are as follows:
[0142] Fig. 9 The 100-cycle charge-discharge cycle test of Example 1 and Example 5 shows that the specific capacity of the battery in Example 5 is always higher than that in Comparative Example 1. The specific capacities of the batteries of both examples are both 140 mAh g -1 above;
[0143] Fig.10 The 100-cycle charge-discharge cycle test of Example 2 and Example 6 shows that the performance of Example 6 is stable and the specific capacity is maintained at 168.73 mAh g -1 The specific capacity of comparative example 2 decays rapidly, and after 100 cycles of charge and discharge, the specific capacity is only 115.92 mAh g -1 .
[0144] Fig.11 The 100-cycle charge-discharge cycle test of Example 3 and Example 7 shows that the specific capacity of Example 7 decays in the first few cycles because the O groups of some PHX molecules undergo irreversible oxidation reactions, resulting in a decrease in specific capacity. After that, the specific capacity of Example 7 stabilizes at 150 mAh g -1 The battery in Comparative Example 3 also decayed in the early stage because part of PHX dissolved in the ionic liquid and then stabilized at 52 mAh g -1 This indicates that the dissolution and precipitation process of PHX reaches a saturated equilibrium state. The battery specific capacity of Example 3 is close to twice that of the battery specific capacity of Comparative Example 3, which further confirms that only the S group of PHX is excited in the liquid electrolyte, while both the S and O groups are excited in the composite polymer solid electrolyte, resulting in Example 7 achieving a battery specific capacity twice that of Comparative Example 3.
[0145] Fig.12 The 100-cycle charge-discharge cycle test of Example 4 and Example 8 shows that the specific capacity of Example 8 reaches 130 mAh g after 100 cycles. -1 This shows that under the condition of composite polymer solid electrolyte, the electrochemical performance of TT is stable, and the specific capacity is further improved around 25 cycles, which may be because the partially blocked ion movement channels in the solid electrolyte are opened; the battery performance of comparative example 4 is also relatively stable, but the specific capacity is reduced from 106 mAh g -1 Down to 87mAh g -1 , indicating that there is still a small amount of TT dissolved in the electrolyte, causing the specific capacity to decay.
[0146] (III) Ratio test
[0147] The button cells prepared in Examples 5 to 8 and Comparative Examples 1 to 4 were subjected to rate tests. The test results are as follows: Figures 13 to 16 As shown, the lists are shown in Tables 3 and 4.
[0148] Table 3 Rate (specific capacity) test results of button batteries prepared in different embodiments / comparative examples
[0149]
[0150] From Table 3 above, it can be seen that the specific capacity of the button battery in the present invention at 1C rate can still reach up to 101.56 mAh g -1 , indicating that the battery rate performance of the present invention is good.
[0151] Table 4 Test results of button cell rate (coulomb efficiency) prepared in different embodiments / comparative examples
[0152]
[0153] It can be seen from Table 4 above that the button cells in Examples 6 to 8 have relatively high coulombic efficiencies at different rates, indicating that the lithium battery in the present invention has excellent stability.
[0154] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be covered by the scope of the claims of the present invention.
Claims
1. A solid-state lithium battery, characterized in that: The solid-state lithium battery includes a positive electrode active material, and the positive electrode active material includes one or more of the diaromatic ring compounds shown in Formula I: In the formula, R1 and R2 are independently selected from S, O or substituted or unsubstituted amino groups, and the substituent of the substituted amino group is an alkyl group.
2. The solid-state lithium battery according to claim 1, characterized in that: The alkyl group is a branched chain hydrocarbon group or a straight chain hydrocarbon group.
3. The solid-state lithium battery according to claim 2, characterized in that: The alkyl group is a straight-chain hydrocarbon group, and the number of carbon atoms in the straight-chain hydrocarbon group is ≤5.
4. The solid-state lithium battery according to claim 1, characterized in that: The diaromatic ring compound is selected from one or more combinations of phenoxathiol, 5,10-dihydro-5,10-dimethylphenazine, 10-methylphenothiazine or thianthrene.
5. The solid-state lithium battery according to any one of claims 1 to 4, characterized in that: The solid-state lithium battery also includes a solid electrolyte, which includes a substrate and an electrolyte material on the surface of the substrate, wherein the electrolyte material includes a polymer and a lithium salt; or the electrolyte material includes a polymer, a lithium salt and an ionic liquid.
6. The solid-state lithium battery according to claim 5, characterized in that: The solid electrolyte meets one or more of the following conditions: (a) the polymer is selected from one or more of PDADMATFSI, PDADMAFSI or PDADMAPF6; (b) the lithium salt is selected from one or more combinations of LiTFSI, LiFSI or LiPF6; (c) The ionic liquid is PYR 13 TFSI and / or PYR 13 FSI; (d) the electrolyte material comprises a polymer and a lithium salt, and the mass ratio of the polymer to the lithium salt is (1-3):(1-2); (e) The electrolyte material includes a polymer, a lithium salt and an ionic liquid, and the mass ratio of the polymer, the lithium salt and the ionic liquid is (1-3): (1-2):(2-3); (f) the thickness of the substrate is 0.03 mm to 10 mm; (g) The substrate is a membrane-like material prepared from natural wood fiber slurry.
7. The solid-state lithium battery according to claim 6, characterized in that: The preparation method of the solid electrolyte comprises: mixing a polymer, a lithium salt, an ionic liquid and a first solvent to obtain a first mixed material; then coating the first mixed material on a substrate, and first drying to obtain a solid electrolyte.
8. The solid-state lithium battery according to claim 7, characterized in that: The preparation method of the solid electrolyte meets one or more of the following conditions: (i) the first solvent is selected from one or more combinations of N-methylpyrrolidone, N,N-dimethylformamide or acetone; (ii) The first drying conditions include: a drying temperature of 30° C. to 100° C. and a drying time of 1 h to 36 h.
9. The solid-state lithium battery according to any one of claims 1 to 4 and 6 to 8, characterized in that: The positive electrode active material also includes a conductive material and a binder.
10. The solid-state lithium battery according to claim 9, characterized in that: The positive electrode active material meets one or more of the following conditions: (A) the conductive material is selected from one or more combinations of SuperP, carbon nanotubes, graphene or conductive carbon black; (B) the binder is selected from one or more combinations of PDADMATFSI, PVDF or sodium alginate; (C) The mass ratio of the diaromatic ring compound, the conductive material and the adhesive is (4-8):(1-5):
1.
11. The solid-state lithium battery according to claim 10, characterized in that: The solid-state lithium battery includes a positive electrode, which includes a positive electrode plate and a positive electrode active material on the surface of the positive electrode plate. The preparation method of the positive electrode includes: mixing the positive electrode active material with a second solvent, grinding to obtain a second mixture; mixing the second mixture with the second solvent to obtain a third mixture; coating the third mixture on the positive electrode plate, and drying to obtain the positive electrode.
12. The solid-state lithium battery according to claim 11, characterized in that: The preparation method of the positive electrode meets one or more of the following conditions: (I) The thickness of the positive electrode active material is 0.025 mm to 10 mm; (II) The positive electrode plate is an aluminum current collector, and the aluminum content of the aluminum current collector is greater than 5%; (III) the second solvent is selected from one or more combinations of solvents selected from N-methylpyrrolidone, N,N-dimethylformamide or acetone; (IV) In the second mixture, the total mass concentration of the diaromatic ring compound, the conductive material and the adhesive is 0.001 g / ml-1 g / ml; (V) The temperature of the second drying is 30°C to 120°C.
13. Application of diaromatic ring compounds as positive electrode active materials for solid-state lithium batteries. The structural formula of diaromatic ring compounds is as follows: In the formula, R1 and R2 are independently selected from S, O or substituted or unsubstituted amino groups, and the substituent of the substituted amino group is an alkyl group.
14. The solid-state lithium battery according to claim 13, characterized in that: The biaromatic ring compound is selected from phenoxathiol, 5,10-dihydro-5,10-dimethylphenazine, 10-methylphenothiazine or thianthrene.
Citation Information
Cited By
Cross-linked conjugated polymer, preparation method thereof and application of cross-linked conjugated polymer in alkali metal battery
CN121248907A